A Review of Muslim-Christian Relations in Light of Bediuzzaman Said Nursi‘s Works - Bisati, Dr. Afroz Ahmad (International Journal of Psychosocial Rehabilitation, 2020)
The article attempts to highlight the views of the Turkish scholar and reformer Said Nursi (1876- 1960 AD) on Muslim-Christian relationship with reference to his writings. The article specifically discerns that the non-legalistic and positive understanding of certain verses of the Qur‟an (5:51) on the subject is unique and of immense significance not only for the healthier cooperation and dialogue between the two communities but also for the world peace at large, as Islam and Christianity are two major contemporary religions.